The effects of an HIIT program on young soccer players` physical performance - Michailidis, Y.; Ganotakis, C.; Motsanos, N.; Metaxas, T. (International Journal of Sports Science & Coaching, 2023)
High-intensity interval training (HIIT) is widely used in soccer. The purpose of the study was to investigate the effect of an HIIT program on the performance of soccer players under the age of 17. Twenty-nine youth players participated in this study. Players were randomly separated into two groups: control group (n = 14) and intervention group which performed extra HIIT (EX, n = 15). The duration of the training program was 4 weeks. Sprint 10 m, 30 m, countermovement jump (CMJ), squat jump (SJ), Illinois agility test, YO-YO intermitted recovery test 1, and repeated sprint ability (RSA) test (RSAbest, RSAmean, RSAdecrement) were measured pre and post the training program. The performance in 10 m, Illinois test, and RSAmean improved in the EX group (P = 0.022, P = 0.047, and P = 0.045, respectively). The performances of the two groups differed significantly in post-measurement of 10 m, Illinois test, and RSAmean (P = 0.046, P = 0.039, and P = 0.044, respectively). This study supports that a short-term program of HIIT can improve acceleration, agility, and RSA performance.